2010
DOI: 10.3233/jad-2010-1308
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Reduces Pathology and Improves Memory in a Transgenic Mouse Model of Alzheimer's Disease

Abstract: We have previously reported anti-amyloidogenic effects of leptin using in vitro and in vivo models and, more recently, demonstrated the ability of leptin to reduce tau phosphorylation in neuronal cells. The present study examined the efficacy of leptin in ameliorating the Alzheimer's disease (AD)-like pathology in 6-month old CRND8 transgenic mice (TgCRND8) following 8 weeks of treatment. Leptin-treated transgenic mice showed significantly reduced levels of amyloid-β (Aβ) 1-40 in both brain extracts (52% reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(183 citation statements)
references
References 37 publications
(47 reference statements)
9
174
0
Order By: Relevance
“…A recent prospective study found that the incidence of AD was much lower in nonobese individuals with high circulating leptin levels [66], which further supports a link between leptin levels and the incidence of this disease. Studies in rodent AD models have also detected correlations between leptin and neurodegeneration as leptin levels are significantly reduced in APPSwe and CRND8 murine models of AD [67,68].…”
Section: Leptin and Neurodegenerative Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent prospective study found that the incidence of AD was much lower in nonobese individuals with high circulating leptin levels [66], which further supports a link between leptin levels and the incidence of this disease. Studies in rodent AD models have also detected correlations between leptin and neurodegeneration as leptin levels are significantly reduced in APPSwe and CRND8 murine models of AD [67,68].…”
Section: Leptin and Neurodegenerative Disordersmentioning
confidence: 99%
“…Another key pathological hallmark of AD is neurofibrillary tangles comprising hyperphosphorylated tau. Recent studies indicate that leptin regulates the levels of phosphorylated tau, as leptin not only reduces neuronal accumulation of tau but also limits tau phosphorylation via inhibition of GSK3b [68]. In cortical neurons, leptin markedly reduces Ab-stimulated increases in phosphorylated tau (p-tau; [69]).…”
Section: Leptin Prevents Synaptic Disruption and Neuronal Cell Death mentioning
confidence: 99%
“…By contrast, rodents do not provide a good model for assessing detrimental effects on LTM. Nevertheless, to date, almost all NOR tests have been done in rodents and this test is increasingly used in rodent animal models of various diseases including Alzheimer's Disease (Donkin et al, 2010;Greco et al, 2010;Hillen et al, 2010;Lu et al, 2009;Mouri et al, 2007;Nishida et al, 2006;Taglialatela et al, 2009), schizophrenia (Hauser et al, 2009;McLean et al, 2009;Neill et al, 2010;Ozawa et al, 2006;Powell et al, 2007;Vigano et al, 2009), and Down's syndrome (Lockrow et al, 2010). The absence of any external reinforcement in the NOR test is particularly important as it makes it more comparable to memory tests in human, which are normally conducted without the use of positive or negative reinforcers such as food and electric shock (Ennaceur and Delacour, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although most rodent models of AD do not fully replicate the pathological and behavioural characteristics of human AD, attenuated circulating leptin levels have also been detected in various AD models [84,85]. Moreover, a transgenic AD mouse model (APP/PS1) with elevated toxic amyloid-β (Aβ) plaques and memory loss, displays a reduction in Ob-R levels as well as key components of Ob-R signalling, including STAT3 and SOCS3 [86].…”
Section: A Link Between Leptin and Alzheimer's Disease (Ad)mentioning
confidence: 99%